(untitled) (Castilla. Estudios de Literatura, 2015)
The purpose of this work is threefold: First, to develop a textual model of literary genres based on generic categories, natural and elemental, capable of being applied to all literary texts, existing or imaginable; second, to attempt to explain the relation between literary genres and fictionality, to show that there are fictional and non-fictional literary genres; third, to build on the theory of possible worlds with a complementary theory of impossible worlds capable of explaining cases of rupture in fictional logic, or metalepsis. The distinct possibilities of rupture in fictional logic will be exemplified, explaining their characteristics and representing them graphically through the proposed textual model of literary genres.